Pengaruh kualitas pelayanan, kualitas produk dan promosi terhadap keputusan pembelian Aki Merk SG pada PT Jaya Timur - Kennedy Yap, Jonh; Purba, Tiurniari (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The customer's purchase decision is beneficial for the company because it will be the final direction the company gets. As a result, the company must try to move more actively in terms of attracting the attention of customers in order to increase the company's margins and meet the company's needs, desires, and purchasing decisions and gain pleasure in the hearts of customers so that customers are expected to be loyal. The population in this study were consumers of PT Jaya Timur brand SG batteries. The total population of consumers purchasing SG brand batteries at PT Jaya Timur is a total of 2460 consumers. The size of the sample from a population can be determined by using the Slovin formula so that the sample taken in this study is 188 respondents. The results of the t-test show that the service quality variable has a t-count value of 3.363 with a significance level of 0.001 <0.05. The product quality variable shows a t-count value of 3.323 with a significance level of 0.001<0.05. The promotion variable shows a t-count value of 16,247 with a significance level of<0.05. The F test results show that Service Quality, Product Quality and Promotion have a simultaneous positive and significant effect on Purchase Decisions with a significance number of 0.000 <0.05. The coefficient of determination (Adjusted R Square) is 0.674 or 67.4% of the purchasing decision variables. can be explained or influenced by service quality, product quality and promotion.